2006
DOI: 10.1097/01.mlg.0000233508.06499.41
|View full text |Cite
|
Sign up to set email alerts
|

The Endoscopic Management of Zenker Diverticulum: CO2 Laser versus Endoscopic Stapling

Abstract: The endoscopic management of ZD is a safe and effective technique. The endoscopic stapling technique appears to have an improved efficacy and safety when compared with the CO2 laser technique. The two techniques are compared and contrasted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 15 publications
3
67
2
3
Order By: Relevance
“…In a recently published article, Miller et al [16] showed that the endoscopic stapling technique has better efficacy and safety than the CO 2 laser technique.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recently published article, Miller et al [16] showed that the endoscopic stapling technique has better efficacy and safety than the CO 2 laser technique.…”
Section: Discussionmentioning
confidence: 98%
“…Its advantages over the standard open-neck technique, as reported in many series [9][10][11][12][13], include a shorter operative time, hospital stay, and interval from surgery to oral intake as well as a lower rate of complications, lower morbidity and mortality rates, and decreased costs [14,15]. Furthermore, the endoscopic stapled diverticulostomy (ESD) was found to be superior also to the other endoscopic approaches (carbon dioxide [CO 2 ] laser and cautery) in terms of safety and efficacy, in addition to the lower recurrence rate offered by the cautery technique [15,16].…”
mentioning
confidence: 95%
“…We identified 6,915 patients from 93 studies evaluating the effect of the surgical treatment for ZD, including 52 studies [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59] (n = 3,336) on endoscopic surgeries, 22 [60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81] (n = 2,204) on open surgeries, and 19 [3,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,…”
Section: Search Resultsmentioning
confidence: 99%
“…Both Veronique et al and Miller et al compared carbon dioxide laser diverticulostomy with endoscopic staple-assisted diverticulostomy. Both of these retrospective analyses revealed improved efficacy, safety, and a shorter duration of hospitalization postoperatively with the stapling technique [4,5]. One complication that was significantly lower in the staple-assisted technique was the presence of postoperative extraesophageal air.…”
Section: Discussionmentioning
confidence: 99%
“…Use of the GIA, by comparison, was associated with postoperative free air in 9% of patients. Another study revealed lower complication rates altogether in the GIA stapler group versus the CO 2 laser cohort, 11% versus 31%, respectively, with 19% of patients in the CO 2 laser group experiencing subcutaneous emphysema postoperatively compared with 0% in the GIA stapler group [4]. We used a combined endoscopic approach to treat this patient, using a GIA stapler followed by CO 2 laser myotomy.…”
Section: Discussionmentioning
confidence: 99%